A minimally invasive clinical model to test sunscreen toxicity based on oxidative stress levels using microbiopsy and confocal microscopy – a proof of concept study. (30th August 2020) - Yamada, Miko; Lin, Lynlee L.; Hang, Lydia Y.T.; Belt, Paul J.; Peter Soyer, H.; Raphael, Anthony P.; Prow, Tarl W.
Abstract: Objective: This proof‐of‐concept study demonstrated that using minimally invasive skin microsampling could enable significantly higher throughput of cosmetic testing in volunteers than conventional biopsy. Nanoparticle sunscreen was used as a model to test toxicity based on oxidative stress using microbiopsy and confocal imaging. Methods: Six volunteers were recruited for this study (3 males and 3 females). Zinc oxide nanoparticle containing topical formulation was prepared at 10% w/v. Each volunteer had 3 areas of 4 cm 2 each mapped on each inner forearm for a total of 6 treatment areas (intact/ tape‐stripped and with/without treatment). The topical zinc‐nanoparticle formulation was applied directly to volunteer skin (2mg/cm 2 ) for 2 hrs. Microbiopsied tissue from each treatment group was stained for reactive oxygen and nitrogen species in addition to mitochondrial superoxide. The stained samples were then imaged using confocal microscopy prior to image analysis. Results: Skin exposed to zinc oxide nanoparticles did not show any significant increases in oxidative stress. Zinc oxide nanoparticle tape‐stripped skin resulted in signal significantly lower ( P < 0.001) oxidative stress levels than t‐butylated hydroxytoluene treated tape‐stripped skin for oxidative stress markers. Topically applied zinc oxide nanoparticles had no detectable effect on the oxidative status in volunteer skin. No adverse reactions or effects were observed after all treatments including microbiopsy. Conclusion: The data support the hypothesis that microbiopsy is a viable approach to study cosmeceutical‐ skin interactions in volunteers with capacity for molecular assays and high throughput with very low risk to the volunteer. Abstract : We hypothesize that using minimally invasive skin microsampling could enable significantly higher throughput of cosmetic testing in volunteers than conventional biopsy. This approach could be applied to any topical cosmeceutical product testing to enable high‐quality volunteer data without scarring or pain. This report is the first to apply in vitro analytical methods for determining oxidative stress to sunscreen‐treated volunteers using skin microbiopsy. Résumé: Objectifs: Cette étude de validation de concept a démontré que le microprélèvement cutané minimalement invasif pouvait augmenter considérablement la cadence des essais de produits cosmétiques sur des volontaires par rapport à une biopsie conventionnelle. Un écran solaire contenant des nanoparticules a été utilisé comme modèle pour tester la toxicité liée au stress oxydatif à l'aide de la microbiopsie et de l'imagerie confocale. Méthodes: Six volontaires ont été recrutés pour cette étude (3 hommes et 3 femmes). Une formulation topique contenant des nanoparticules d'oxyde de zinc a été préparée à 10 % p/v. Chaque volontaire disposait de 3 zones de 4 cm 2 situées sur chaque pliure de coude pour un total de 6 zones de traitement (intactes / strippée et avec / sans traitement). La formulation topique contenant des nanoparticules d'oxyde de zinc a été appliquée directement sur la peau des volontaires (2 mg/cm 2 ) pendant 2 heures. Les tissus microbiopsiés de chaque groupe de traitement ont été colorés pour détecter des espèces réactives de l'oxygène et de l'azote en plus de la superoxyde mitochondriale. Les échantillons colorés ont ensuite été examinés par microscopie confocale avant l'analyse des images. Résultats: La peau exposée aux nanoparticules d'oxyde de zinc n'a pas montré de hausse significative de stress oxydatif. La peau strippée traitée aux nanoparticules d'oxyde de zinc a entraîné des niveaux de stress oxydatif nettement inférieurs ( p <0, 001) comparés à ceux de la peau strippée traitée à l'hydroxytoluène t‐butylé en ce que concerne les marqueurs de stress oxydatif. Les nanoparticules d'oxyde de zinc appliquées par voie topique n'ont eu aucun effet détectable sur l'état oxydatif de la peau des volontaires. Aucune réaction ou effet indésirable n'a été observé(e) après tous les traitements, y compris la microbiopsie. Conclusion: Les données obtenues étayent l'hypothèse selon laquelle la microbiopsie est une approche viable pour étudier les interactions des produits cosmétiques sur la peau des volontaires, avec la possibilité de réaliser des dosages moléculaires et à haut débit, avec un risque très faible pour les volontaires.